Pengaruh Pendampingan Orang Tua terhadap Tingkat Stress Hospitality Pasien Pediatric di Rumah Sakit Muhammadiyah Lamongan - Septiliana Dwi Handanyani; Raden Sugeng Riyadi; Nia Handayani (STIKes Ibnu Sina Ajibarang, 2025)
Hospitalization in children can trigger stress and anxiety due to unfamiliar environments, medical procedures, and separation from parents. School-age children (6–12 years old) are particularly susceptible to preoperative stress, which if left untreated can interfere with the anesthesia process and surgical procedures. Parental assistance during the pre-operative phase has the potential to reduce stress levels in pediatric patients. This study aims to determine the effect of parental assistance on the level of hospitalization stress in pediatric patients in the pre-operative room at Muhammadiyah Lamongan Hospital. This study uses a quantitative method with a quasi experiment pre-test and post-test two group design. The sample consisted of 24 children aged 6–12 years, who were divided into two groups: experimental (supervised by parents) and controlled (unsupervised). Sampling was carried out by accidental sampling. The measuring tool used is the Face Anxiety Scale. Data analysis used Wilcoxon and Mann-Whitney tests. The results of the Mann-Whitney test showed a p-value = 0.000 which means that there was a significant difference between the experimental and control groups in the level of hospitalization stress after treatment. This shows that parental mentoring has a significant effect on reducing stress in children before surgery. Parental assistance is effective in reducing hospitalization stress levels in pediatric patients in the preoperative room. Hospitals are advised to create policies that support parental counseling during the pre-operative process, and follow-up research can add control variables for more in-depth outcomes as well as consider psychosocial factors, previous experiences, the type of medical procedures performed, as well as parents' anxiety levels before and during counseling.